General public knowledge, source of knowledge and practice towards antibiotics in the state of penang, Malaysia - Mahmoud Sa'di Al-Haddad (Archives of Global Professionals, 2012)
Objectives: This study aims to investigate the general public knowledge, source of knowledge, and practice towards antibiotics in the state of Penang Malaysia. Methods: A cross sectional study design using convenience sampling technique was adopted in this study from May 2010 until August 2010. A pre-validated questionnaire was developed and distributed to 700 participants in the state of Penang, Malaysia. All data was analysed using SPSS version 16. A p-value of less than 0.05 was considered significant. Results: 85.6% of our respondents could correctly identify that antibiotics are used for bacterial infections whereas almost 58% believed that antibiotics are used for viral infections. Physicians and pharmacists were the main sources of knowledge about antibiotics. While around 30% of our respondents rely on the internet, family members and friends as their sources of information about antibiotics. Malpractice regarding antibiotics use was found in a high proportion of our respondents where many use antibiotics without prescription, prescribe the leftover antibiotics to their friends and family members while others modify the antibiotics dose without referring to healthcare professional and others stop the antibiotics course once they feel that their symptoms improve. Conclusion: Malpractice regarding antibiotics was found in a great proportion of our respondents which might be due to the irrational prescription of antibiotics by healthcare professionals as well as due to the misleading sources of knowledge about antibiotics. There is a need for a national awareness program to the public and healthcare professionals about antibiotics and about the approaches to improve the current practice.